Quantification of Aryltetralin Lignans in Linum album Organs and In Vitro Cultures: Lignans from Linum album - Mohagheghzadeh, Abdolali; Hemmati, Shiva; Alfermann, A. Wilhelm (Iranian Journal of Pharmaceutical Sciences, 2006)
Aprocedure was developed for rapid in vitro germination of Linum album seeds by scarification and exposing to gibberellic acid (GA3) and kinetin (Kn). Concentrations of podophyllotoxin (PTOX) and related aryltetralin lignans α-peltatin, β-peltatin, 5’-demethoxy-6-methoxypodophyllotoxin and 6-methoxypodophyllotoxin (MPTOX) in L. album fresh plant organs were determined by HPLC. A degree of variation was observed in lignan content in different plant parts and growth stages. It was found that PTOX is predominant in productive organs and leaves. The highest amount of PTOX (0.651 mg/100g dry wt.) and MPTOX (0.670 mg/100g dry wt.) and the total quantified lignans were found in the capsules. In vitro cultures were studied for lignans followed by high productive cell line selection. Calli cultures were more productive for MPTOX than PTOX, while suspension cells accumulate comparable amounts of PTOX and MPTOX. The highest amount of PTOX (0.301% mg/g dry wt.) was found in suspension originated immobilized cultures.